Risk Factors for Cement Leakage and Adjacent Vertebral Fractures in Kyphoplasty for Osteoporotic Vertebral Fractures. Issue 6 (July 2020) - Chen, Changhong; Fan, Pan; Xie, Xinhui; Wang, Yuntao
Abstract : Purpose: Cement leakage and adjacent vertebral fractures are not uncommon after percutaneous augmentation. However, conclusive identification of risk factors for postprocedural complications remains elusive. The anticipation of leakage and successive fractures through the identification of risk factors will help physicians better inform patients of potential complications and establish procedural refinements key to risk reduction. The aim of this retrospective study was to summarize available reports of the risk factors for cement leak and adjacent vertebral fracture in or after kyphoplasty for osteoporotic vertebral compression fractures. Methods: A total of 102 cases of bilateral percutaneous kyphoplasty (PKP), performed between January 2014 and December 2016, were retrospectively reviewed. Each case surveyed in this review included a minimum 1-year follow-up and data on age, sex, bone mineral density, Visual Analog Scale score, preoperative compression rate, kyphotic angle, treatment time, the volume of cement, and the intactness of the vertebral posterior wall (computed tomography scan) were collected. Pearson χ 2 test and independent samples test were used to determine the relative risk factors of cement leak and adjacent vertebral fracture in patient subsets. Results: Diabetic status and alteration in the Cobb angle after PKP exhibited a statistically significant correlation with the incidence of new adjacent vertebral fracture (group B) ( P <0.05). In addition, the integrity of vertebral walls ( P =0.001) and the volume of injected cement ( P =0.026) significantly boosted the potential risk of cement leakage ( P <0.05), although these variables did not associate with the adjacent fracture. Additional examined variables, including age, sex, Visual Analog Scale scores, number of fractures were not significantly associated with leakage or adjacent vertebral fracture risk. Conclusions: Diabetes and the alteration of the Cobb angle following PKP are factors positively related to the occurrence of postoperative adjacent vertebral fractures. It is also demonstrated that the integrity of vertebral walls and average volumes of injected cement are the possible risk factors of cement leakage while performing the PKP.